Natural Frequency of Lightweight Composite Slabs Based On Experimental Study and Numerical Modelling - Jaini, Z. M.; Sugiura, K.; Abdul Kudus, S.; Rum, R. H. M.; Hakim, S. J. S.; Abd Ghafar, N. H. (International Journal of Integrated Engineering, 2023)
Recently, lightweight composite slabs have become increasingly popular. Lightweight composite slabs are an innovation that provides a better and more convenient construction method for floor systems. Under dynamic loads, lightweight composite slabs may experience meagre inertia forces due to poor stiffness or low mass. Compared to conventional composite slabs, lightweight composite slabs are 40% lighter and more susceptible to structural resonance. Therefore, the vibration behaviour must be controlled to avoid discomfort issues. This study investigates the natural frequency of lightweight composite slabs through experimental study and numerical modelling. In the experimental study, lightweight composite slabs were prepared for the hammer-impact test. The slab thickness ranges from 100 mm to 200 mm. In numerical modelling, lightweight composite slabs were modelled in SAP2000 using a unique technique called the simplified equivalent plate model. The effective material properties were derived from the rule of mixtures and depend exclusively on elastic properties with strength characteristics. The results of the experimental study and numerical modelling agree positively. The natural frequency decreased with slab thickness, signifying that the natural frequency is dominated by mass rather than stiffness. Overall, the natural frequency of lightweight composite slabs is around 27.23Hz to 31.45Hz.